2017
DOI: 10.1002/pd.5034
|View full text |Cite
|
Sign up to set email alerts
|

The recurrence of sonographic ‘soft markers’: ominous sign or ‘just’ genetics?

Abstract: The high recurrence rate of solitary SM implies for genetic predisposition. These results might improve our counseling for pregnant women affected by the reappearance of solitary SM. Further studies are needed to assess the likelihood ratio for SM if recurrence occurs. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…USMs are detected during fetal sonographic anatomical screening in approximately 10% of normal fetuses in the USA 17 . Ginsberg showed that there is a high recurrence rate of solitary USMs, which supports the hypothesis that genetic factors form the basis for the reappearance of USMs 18 . Therefore, there were different incidences of USMs among fetuses of different races.…”
Section: Discussionsupporting
confidence: 56%
“…USMs are detected during fetal sonographic anatomical screening in approximately 10% of normal fetuses in the USA 17 . Ginsberg showed that there is a high recurrence rate of solitary USMs, which supports the hypothesis that genetic factors form the basis for the reappearance of USMs 18 . Therefore, there were different incidences of USMs among fetuses of different races.…”
Section: Discussionsupporting
confidence: 56%
“…However, the detection of USMs cause stress in pregnant women, and the depressive symptoms may persist until delivery ( Ahman et al, 2010 ; Nevay et al, 2016 ). Previous studies have shown that USMs, such as EICF, thickened nuchal fold, and mild pyelectasis were commonly repeated in subsequent pregnancies, providing deeper insights into the genetic predisposition and recurrence of USMs ( Ginsberg et al, 2017 ). In particular, the interpretation of abnormal results and clinical genetic consultation in pregnant women who have had USMs and undergone NIPS may also cause confusion for them and the clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Cordocentesis is associated with a risk of complication; the foetal loss rate within 2 weeks in the study was 0.47%, lower than that reported in other studies, in which cordocentesis was performed in pregnancies with a gestational age of < 24 weeks (early cordocentesis is more difficult and has a tendency to increase the rates of adverse outcomes) [7]. Ultrasound soft markers are defined as minor nonspecific findings on ultrasound scans, which are often transient and have little or no pathological significance, such as an echogenic intracardiac focus, a thickened nuchal fold and an echogenic bowel; although not pathological per se, ultrasound soft markers have been found to be linked to foetal aneuploidies such as Down syndrome [8]. In this study, the most common indication for diagnostic genetic testing was ultrasound soft markers, which accounted for 73.16% of the indications, and the rate of foetal chromosome abnormality was 2.02% (50/ 2478).…”
Section: Discussionmentioning
confidence: 99%